Topic B: Magma flow and emplacement (Journal of the Czech Geological Society, 1995)
Abstracts to the International conference on Thermal and Mechanical Interactions in Deep Seated Rocks Abstracts to the International conference on Thermal and Mechanical Interactions in Deep Seated Rocks, September 27 - October 1, 1995, Prague, Czech Republic